2020
DOI: 10.1101/2020.02.14.948877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motor training strengthens corticospinal suppression during movement preparation

Abstract: 46Motor training improves the efficiency of trained movements and modifies neural activity 47 at rest and during motor execution. Training may also shape preparatory processes but the neural 48 correlates and the potential behavioral relevance of changes at the level of action preparation 49 remain unclear. In humans, transcranial magnetic stimulation (TMS) studies have shown that 50 movement preparation is accompanied by a suppression of corticospinal (CS) excitability relative 51 to a baseline measure; a phe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 84 publications
3
23
0
Order By: Relevance
“…Interestingly, an age-related reduction in resting-state intra-cortical inhibition is suggested to predict a reduced capacity to modulate inhibitory processes during a motor task, which relates to motor function declines ( Heise et al, 2013 ). In our experiment, however, we did not probe baseline measures at complete rest, but at the start of each trial to control for the processes related to the task-driven increases in attention ( Kastner et al, 1999 ; Labruna et al, 2011 ; Vassiliadis et al, 2020 ). An interesting hypothesis for future research would be to investigate to what extent our observed relation between motor performance and (dis)inhibitory fronto-motor modulations are driven by the inhibitory state measured at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an age-related reduction in resting-state intra-cortical inhibition is suggested to predict a reduced capacity to modulate inhibitory processes during a motor task, which relates to motor function declines ( Heise et al, 2013 ). In our experiment, however, we did not probe baseline measures at complete rest, but at the start of each trial to control for the processes related to the task-driven increases in attention ( Kastner et al, 1999 ; Labruna et al, 2011 ; Vassiliadis et al, 2020 ). An interesting hypothesis for future research would be to investigate to what extent our observed relation between motor performance and (dis)inhibitory fronto-motor modulations are driven by the inhibitory state measured at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the lack of effect of reward on RTs may arise, however, if one concedes that this measure not only reflects the speed of action selection but also the rapidity of sensory processing (Haith et al, 2016;Vassiliadis et al, 2020), and that reward could have affected these two processes in opposite ways. Indeed, the task described above puts a considerable demand on sensory processing, as it required participants to discriminate between four target locations and, in some trials, to avoid distractor cues.…”
mentioning
confidence: 99%
“…This preparatory inhibition may reflect a form of volitional proactive inhibition that prevents premature release of the intended movement; alternatively, it may represent a necessary part of preparing to move. Given that the suppression occurs regardless of proactive inhibition (RDE), it is more likely that CSE suppression at the time of the go cue represents a necessary part of movement preparation (Vassiliadis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%